The Traces of Islamization and Cultural Acculturation in the Sultanate of Palembang (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2025)
The civilization of the Palembang Sultanate era underwent a long historical journey, beginning with the golden age of Srivijaya, the fall of Srivijaya, Palembang's prominence as a trade center, the era of the Palembang Sultanate, and eventually the arrival of Dutch colonial rule. Islam was introduced to Palembang in the 16th century and quickly flourished, transforming the social and political structures of the local community. This article employs qualitative descriptive research with descriptive procedures and techniques, focusing on data sourced from literature, particularly relevant works addressing the subject of study. The findings reveal that the transformation during the Palembang Sultanate era reflects the social, economic, and cultural dynamics shaped by interactions between global influences and local traditions, establishing Palembang as one of the significant centers of Islamic civilization in Indonesia.